A Receipt-Free i-Voting System Based on Blind Signatures and Anonymous IDs - Barros, Charles F. de; Pimenta, Diego F. (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2018)
In this paper, we propose an i-voting scheme based on blind signatures, with a mechanism to prevent voters from generating vote proofs. The scheme combines blind signatures of the ballots with anonymous IDs also blindly signed by the election authority. After the election is closed, the list of ballots and corresponding signatures is published by the election authority, allowing any interested party to check the integrity of the result.